Designing public squares with green infrastructure to optimize human thermal comfort. (February 2019) - Zölch, Teresa; Rahman, Mohammad A.; Pfleiderer, Elisabeth; Wagner, Georg; Pauleit, Stephan
Abstract: People living in cities are experiencing summerly heat stress situations with severe consequences for their health, especially under climate change. Urban planning needs to address this problem focusing on areas where people are exposed to heat such as in public squares. Typical square designs include green infrastructure which can positively affect outdoor thermal comfort by providing regulating ecosystem services, but knowledge on the effectiveness of different design approaches is still limited. The present study assessed typical greening designs of rectangular public squares and their microclimatic influences during a hot summer day both during day and night-time conditions. By using a validated ENVI-met V4 model, thermal comfort values expressed by the physiologically equivalent temperature (PET) index were compared. Moreover, a novel greening design was developed and tested with the model. The results showed that at 3pm the greening design with most trees and trees placed in the sunlit areas of the square provided 5.2% higher cooling effect compared to the current greening, whereas for 4am the design without trees, but with meadow areas performed best (4.2% heat reduction). This led to the conclusion that for a comfortable thermal situation a climate adapted design has to include trees to maximize the shaded surface areas, while the main wind channel is kept free from trees, but planted with grass to minimize the heat storage. The number of trees and their placement together with the extent and placement of grass areas can thus serve as indicators for designing climate adapted public squares. Highlights: The summerly cooling potential of public squares depends on their greening design. Typical and novel designs for public open spaces were tested with ENVI-met. At daytime designs with a maximum shaded area provide best thermal conditions. At night unhindered air flow and reduced heat storage in meadows performed best. Trade-offs between them need to be considered for designing climate adapted cities.